2005
DOI: 10.1111/j.1600-0714.2005.00281.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural and morphometrical study in glandular parenchyma from alcoholic sialosis

Abstract: These results indicate that the significant variations together with the histological qualitative pattern could be useful as confident indicators for the differential histopathological diagnosis with other sialosis from different aetiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 11 publications
3
15
1
Order By: Relevance
“…Interestingly, related findings were previously observed in patients with alcoholic sialadenosis (Carranza et al , ). Sialadenosis is non‐inflammatory, non‐neoplastic condition, characterized by salivary gland enlargement, and it particularly involves parotid glands.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Interestingly, related findings were previously observed in patients with alcoholic sialadenosis (Carranza et al , ). Sialadenosis is non‐inflammatory, non‐neoplastic condition, characterized by salivary gland enlargement, and it particularly involves parotid glands.…”
Section: Discussionsupporting
confidence: 78%
“…More recently, Carranza et al (2005) showed a significant difference between patients with alcoholic sialadenosis and controls in a number of measured parameters. More specifically, the area occupied by cell in acinus of Blandin-Nuhn, von Ebner, and labial salivary glands, together with the area of one acinar cell in the same salivary glands, was significantly higher in patients with alcoholic sialadenosis.…”
Section: Oral Diseasesmentioning
confidence: 98%
See 1 more Smart Citation
“…Some authors agree that the parotid glandular enlargement in alcoholic cirrhosis patients could be due to the presence of voluminous acini (8,13,28,29). In this sense, a previous study has demonstrated an increase of acinar dimensions in the submaxilar and minor salivary glands of patients with terminal alcoholic hepatic cirrhosis (7). Nevertheless, other studies refer that acinar hypertrophy is absent in the parotid gland of chronic alcoholics (25,26,30).…”
Section: Introductionmentioning
confidence: 97%
“…This pathology does not have predominance according to sex and it is evident generally in people older than 30 years (4)(5)(6). Sialosis is clinically characterized by a bilateral enlargement and painless of the parotid gland, although sialosis also affects in diverse degrees the other greater and smaller glands (1,(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%